การถอดบทเรียนการพัฒนาทักษะชีวิตสำหรับบุคคลออทิสติกในมุมมองผู้เชี่ยวชาญ - ขันสำโรง, ฐาวรี (Community and Social Development Journal, 2016)
This study is based on the methodology of qualitative research. The purpose of this study was to draw up the lesson learnt from developing the long life skills for the persons with autism spectrum disorder on the views of the autism expertsA focus group was used as the research instrument. The qualitative data was collected and analyzed with content analysis technique. The results of this research were found that the person with autism wanted the parents or caregivers to consider autistic children as general people that face problems and try to nd the solution. Viewing them as the same as the others was the great way to support and encourage them to improve themselves. However, the child psychiatrist and the psychiatric nurse practitioner pointed out that the key coordinated roles were assessment, diagnosis and treatment; moreover, the most important process was to nd out the riskiness of being autistic during the rst 3 years olds. Furthermore, the occupational therapist viewed that a fundamental treatment was to solve their ve sensory awareness in integrated way. Moreover, the special education teacher added that if they would go to a school, a co-operation between a school and parents was needed in order to closely take care of their development and study. This helps them to live as normal or close a life as possible.